2019
DOI: 10.1097/md.0000000000015776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Qigong on self-rating depression and anxiety scale scores of COPD patients

Abstract: Objective: To explore the clinical efficacy and safety of Qigong in reducing the self-rating depression scale (SDS) and self-rating anxiety scale (SAS) scores of patients with chronic obstructive pulmonary disease (COPD). Methods: We searched CNKI, Wan fang, Chongqing VIP, China Biology Medicine disc, PubMed, Cochrane Library, and EMBASE for studies published as of Dec 31, 2018. All randomized controlled trials of Qigong in COPD patients, which met the inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Previous studies have shown promising effects of Tai Chi or Qigong exercise on improving depression and anxiety among various populations, including healthy adults [36][37][38][39], and clinical patients with cancer [40], fibromyalgia [41], and chronic obstructive pulmonary disease [42]. There are some systematic reviews examining the efficacy of mindful-based treatment for alcohol and substance abuse [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown promising effects of Tai Chi or Qigong exercise on improving depression and anxiety among various populations, including healthy adults [36][37][38][39], and clinical patients with cancer [40], fibromyalgia [41], and chronic obstructive pulmonary disease [42]. There are some systematic reviews examining the efficacy of mindful-based treatment for alcohol and substance abuse [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…As a category of complementary and alternative medicine, acupressure therapy and Liu Zi Jue Qigong exercises are performed widely in TCM [35,36]. Some researchers have confirmed that they can improve the clinical symptoms and physical and mental health of patients with lung disease [10,37,38]. As the health care system is overloaded, a TCMR program is highly operable and cost-effective [39].…”
Section: Discussionmentioning
confidence: 99%
“…As a category of Complementary and Alternative Medicine, acupressure therapy and Liuzijue Qigong exercise are performed widely in TCM 33,34 . Some researchers have confirmed that they can improve the clinical symptoms and physical and mental health of patients with lung disease [35][36][37] . As for the health care system are overload, the TCMR program is highly operable and cost-effective 38 .…”
Section: Discussionmentioning
confidence: 99%